The Ai Evolution In Higher Education: Enhancing Teaching With Chatgpt - Houda Boumediene (The Journal of Studies in Language, Culture and Society, 2025)
ChatGPT has been making a significant impact and has sharply divided educators, researchers, and educational institutions about its transformation of learning. When integrated properly into teaching and learning activities, ChatGPT can complement the benefits of digital technologies. It provides personalized, adaptive support to learners and educators as an intelligent learning assistant. Unethical use, however, entails serious concerns in relation to academic integrity and assessment practices. Educators' attitudes, expectations, and concerns are the major keys to determining whether such tools are successfully adopted in an educational setting. This study is an attempt to examine the perceptions of university professors at the University of Laghouat, Algeria, on opportunities and challenges facing the use of ChatGPT in teaching. Findings from the survey showed that the majority of professors expressed positive views about adopting ChatGPT in their practices of education (61.2%). The top advantages noted by professors are the potential of this AI tool to automate time-consuming tasks (72.5%), increase student engagement (65.3%), and promote critical thinking and creativity (58.4%). However, there are strong concerns: 83.2% of respondents are afraid that students would become overdependent on ChatGPT without checking the authenticity of the generated content, which may prohibit the development of important knowledge and skills. These findings underline the need for balanced integration strategies, leveraging the potential of ChatGPT to improve teaching and learning while addressing its risks. Only through fostering digital competencies and setting ethical guidelines can institutions guarantee the effective and responsible use of ChatGPT in education.